Engenharia erótica, arquitetura dos prazeres: cartografias da pegação em João Pessoa, Paraíba. - Oliveira, Thiago de Lima (2016)
This dissertation aims to contribute to the growing debate in the Social Sciences about the interactions between people and places from the proposition of ethnographic reflections on erotic narratives and experience of men engaged in a network of affective and sexual changes called "pegação” (cruising). This network is made up of a multiplicity of agents and circuits that are distributed between the public, private, commercial, virtual and domestic spaces. The circuits that make up the network can be defined from fields and models of relationship, even if from crossing and overlap constantly, configure specific ways to understand the meanings produced in the experience. In the dissertation I seek to describe and analyze encounters produced from spaces like bathrooms, beaches, porn cinemas, saunas, websites and mobile apps. The analyze indicates to the way the space and the social markers of difference are intertwined, producing mutual relationships and meanings from erotic economies that value and (re)produce expectations about gender, race, class and generations from strategies of differentiation and fragmentation of the space to different public and interests.